Functional imaging and modeling of the heart : 8th International Conference, FIMH 2015, Maastricht, the Netherlands, June 25-27, 2015. Proceedings /: 8th International Conference, FIMH 2015, Maastricht, the Netherlands, June 25-27, 2015. Proceedings. (2015) - Unknown
No abstract available